(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The Andhra Pradesh State Government Flagship Programmes named Navaratnalu, an ambitious and comprehensive welfare and development programs that were launched by Andhra Pradesh State Government, India. This Flagship programmes initiative, introduced by the Yuvajana Sramika Rythu Congress Party (YSRCP) led and founded by present Chief Minister Y.S. Jagan Mohan Reddy, he aims to address multifaceted challenges and also propel the Andhra Pradesh state towards holistic progress and development. The Navaratnalu Flagship programs encompasses almost nine key areas in different fields, each programme targeting a specific aspect of development, empowerment, social justice, and well-being. These nine pillars by the Navaratnalu are envisioned to collectively transform the Andhra Pradesh state by fostering inclusive growth and also ensuring for the upliftment of every section of people in the society. The following Programmes such Amma Vodi, Vidya Deevena, Vasathi Deevena and Nadu Nedu projects are the three Major schemes that are contributing to the School, Intermediate and also Higher Education System in the state of Andhra Pradesh. This research Paper discusses all the educational related schemes that are introduced through Navaratnalu by the Government of Andhra Pradesh.